Estudo da aplicação da técnica de eletrofloculação na remoção da cor em misturas de corantes têxteis - Tones, Aline Raquel Müller (2015)
This study aimed to apply the electrofloculation technique in aqueous solution consisting of the mixture of textile dyes, Turquoise and Red Scarlet investigating the effect of electric current, treatment time and aluminum dissolved in relation to the color removal. The analysis of the color removal was obtained from the deconvolution method of the absorption spectra in the visible region separating the two dyes of the absorption bands. Subsequently, it was set up a photovoltaic system to use energy as a power source in electrofloculation technique. For the research, the experimental procedure was performed in two stages. In the first stage, tests were conducted based on central composite rotational design (CCRD), consisting of 12 trials run in duplicate, in order to optimize the process. Electrical current and treatment time were used as independent variables, obtaining, as the dependent variable, the percentage color removal centers in three separate absorbers. In the second stage was used the energy from photovoltaic panel, coupled directly to galvanic anode with electrical current and treatment time optimized, obtained in the first step. This procedure was applied to the mixture solution and synthetic sewage in two different weather conditions: on a clear sky day and on a partly cloudy day. It was found that the use of the deconvolution method was feasible, it was possible to perform the separation of absorbing centers and to identify the optimal current and the treatment time in the color removal process for each of the dyes in the mixture. Using the optimal time of 16 min and the current 0,33A were obtained an average percentage of removing over 90% for both dyes. Regarding the use of alternative energy, it is concluded that the use of photovoltaic panel as a power source in Electrofloculation technique applied in the treatment of textile effluents is feasible, resulting in up to 99% color removal on clear skies and 97 day % on partly cloudy sky.